Short Report: Description and Distribution of Wagtails "Family Motacillidae" with Reference to Pakistan - Nadia Yousaf; Kainaat William; Madeeha Manzoor; Balqees Khanum (Journal of Bioresource Management, 2015)
In the current study, Wagtails of the Family Motacillidae were studied in Pakistan. Thirteen species and sub-species were found in different regions. Their characteristics were observed, photographs were taken, previous distributions of these species were analyzed, and a new distribution of each species was reported in this study. During study, the scavenging role of these birds was identified, and it was hoped that wagtails may play an important role in the absence of the vultures after recent downfalls in major scavengers. However, these important effects were not observed in the wagtails, and probably will not occur until their populations increase considerably.